Strategi Pemasaran Digital Yang Efektif Untuk Meningkatkan Daya Saing Perusahaan di Era Digital - Irena Dinar Vania Sasikirana; Aulia Safira Dewi; Queena Aurora Khayzuran; Sabrina Puspa Firdausy; Denny Oktavina Radianto (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Background: In an increasingly competitive digital era, digital marketing strategies are the key to increasing a company's competitiveness. Companies must be able to utilize digital platforms and media effectively to reach a wider audience and build closer relationships with consumers. This research aims to identify effective digital marketing strategies in increasing company competitiveness in the digital era. By understanding the latest trends and technology in digital marketing, companies can develop strategies that are more targeted and responsive to the rapidly changing business environment. Method: This research uses a literature review method to collect and analyze various literature related to effective digital marketing strategies. Results: Digital marketing has become a key element in modern marketing strategies, leveraging digital platforms and media to reach audiences effectively. This paradigm shift is triggered by consumer behavior patterns that are more digitally connected, using the internet and social media to search for information, interact with brands and make purchases. Digital marketing strategies have many benefits, including increasing brand visibility, expanding market reach, increasing consumer engagement, and optimizing user experience. Digital marketing trends continue to evolve, with the use of social media, video-based content, AI, and machine learning as key factors influencing how companies market their products or services.